Estimation of emissions of air pollutants in the Krapina-Zagorje county - Šorgić, Božica (Array, 2019)
The Program for the protection of air quality, ozone layer, climate change mitigation and adaptation of the Krapina-Zagorje County is prepared in accordance with the Article 12 of the Air Protection Act (OG 130/11, 47/14, 61/17, 118/18). The Program sets targets and measures by priority sectors, deadlines and responsible authorities for measures implementation over a five-year period in the County. For the purpose of defining protection measures, based on available data, estimation of annual emissions of pollutants into air was performed: nitrogen oxides, carbon monoxide, sulphur oxides, particles, volatile organic compounds, ammonia, carbon dioxide, methane and dinitrogen monoxide from the main sectors. Emissions were estimated using the EMEP/EEA methodology and 2006 IPCC Guidelines for National Greenhouse Gas Inventories methodology. Road traffic emissions were estimated using DEFRA/DECC methodology. Based on the results on estimated pollutant emissions in the County, appropriate measures have been defined for the protection and improvement of air quality.